2011
DOI: 10.1089/pho.2009.2685
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Laser Phototherapy in the Inflammatory Process of the Rat's TMJ Induced by Carrageenan

Abstract: It was concluded that the LPT presented positive effects on inflammatory infiltration reduction and accelerated the inflammation process, mainly with IR laser irradiation. The number of synovial cell layers was reduced on irradiated group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
3
18
0
9
Order By: Relevance
“…However, these biological agents have various side effects that limit the clinical use (18). From this aspect, LLLT can be considered as an alternative noninvasive treatment with its potential anti-inflammatory and analgesic effects (12,13,(18)(19)(20)(21) This study included patients with pain or moderate disability and discomfort during daily activities on baseline examination, associated with AS. Our results did not show any statistically significant improvement between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, these biological agents have various side effects that limit the clinical use (18). From this aspect, LLLT can be considered as an alternative noninvasive treatment with its potential anti-inflammatory and analgesic effects (12,13,(18)(19)(20)(21) This study included patients with pain or moderate disability and discomfort during daily activities on baseline examination, associated with AS. Our results did not show any statistically significant improvement between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that LLLT can reduce inflammation through inhibition of PGE 2 formation and suppression of cyclooxygenase 2 in human gingival fibroblasts. 8 Carvalho et al 9 reported that infrared laser therapy reduced inflammatory infiltration and accelerated the inflammation process in the rat TMJ injected by carrageen. Lin et al 10,11 reported that HeNe laser (632.8 nm) improved histopathological changes and enhanced the repair and biosynthesis of arthritic cartilage in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effects of LLLT include the modulation of inflammatory processes, analgesia and cellular activity [1-3,6,7,11-13,19-25]. Despite the reported benefits [1-3,6,11,20-22], few studies have analyzed the effects of LLLT administered to adolescents with a diagnosis of TMD [1-3,6,7,11-13,20-25]. …”
Section: Introductionmentioning
confidence: 99%